36th AIAA Plasmadynamics and Lasers Conference 2005
DOI: 10.2514/6.2005-5172
|View full text |Cite
|
Sign up to set email alerts
|

Direct Impulse Measurements of Ablation Processes from Laser-Surface Interactions

Abstract: A torsional impulse balance has been developed as a new diagnostic tool to study fundamental processes in laser-surface interactions. Of particular interest are the forces due to processes of laser ablation. With respect to the transfer of momentum, direct measurements of the transient forces can lead to a better understanding and characterization of the efficiency of the impulse that is possible under different configurations. The impulse balance has been designed and tested with a robust calibration system t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
(1 reference statement)
1
4
0
Order By: Relevance
“…The values of laser generated impulse and the corresponding C m measured here are similar to those obtained in other works on aluminum [6,12,13]. Anyway, a precise comparison still remains difficult due to the different experimental conditions of these works, namely longer laser wavelength (532 nm or 1064 nm), different pulse duration, and pressure.…”
Section: Comparison With Other Apparatuses In Literaturesupporting
confidence: 81%
See 1 more Smart Citation
“…The values of laser generated impulse and the corresponding C m measured here are similar to those obtained in other works on aluminum [6,12,13]. Anyway, a precise comparison still remains difficult due to the different experimental conditions of these works, namely longer laser wavelength (532 nm or 1064 nm), different pulse duration, and pressure.…”
Section: Comparison With Other Apparatuses In Literaturesupporting
confidence: 81%
“…As reported in literature, impulse and C m measurements generally exploit system based on ballistic pendulums [5,[13][14][15][16][17], torsion pendulums [4,12], and load cells [6,11,[18][19][20], with typical uncertainties of about 10% on both impulse and C m . The apparatus described in this work allows measurements with uncertainties of 1%, a result that can be mainly attributed to the choice of using a specifically designed ballistic pendulum and to the system used to detect its motion.…”
Section: Comparison With Other Apparatuses In Literaturementioning
confidence: 99%
“…It is well known that the impulse performance is strongly affected by the initial humidity and contamination on the target sample surface [2,21]. To suppress experimental uncertainty, a series of cleaning shots were routinely conducted before irradiating with the primary laser pulse; 10 laser pulses with a fluence of 0:25 J=cm 2 , which was high enough for the cleaning and lower than the ablation threshold of POM of about 0:4-1 J=cm 2 [22], were irradiated without the focusing lens [23].…”
Section: Methods Of Impulse and Mass Measurementmentioning
confidence: 99%
“…Moreover, this characteristic is consistent with the relationship between C m and φ p when using normal single laser pulse irradiation to a virgin surface. 5) However, the changing coincide with crater generation is not only due to the changing surface area. Other factors such as oblique incidence, the confinement effect of the crater, 13) directionality of ablation impulse on the inner wall of the crater, and resolidification of melted Al ejected from the bottom region near the entrance of the crater, may all affect the impulse with repetitive irradiation.…”
Section: Influence Of Crater Deepening On the Impulsementioning
confidence: 99%
“…Several authors have reported that C m increased to the peak value and then decreased while increasing the fluence of the laser pulse, which is the energy density in the illuminated area. 4,5) Compared with a continuous-wave laser, the pulsed laser is more advantageous in such missions because it is much easier to reach the high intensity needed to iniciate ablation on the target, and the plasma shielding effect 6) with pulse laser shooting is not so serious. For ns-pulsewidth laser irradiation, the optimized laser fluence is at the level of 10 J/cm 2 .…”
Section: Introductionmentioning
confidence: 99%